Principal functions of non-selfadjoint discrete Sturm-Liouville equations with quadratic spectral parameter in boundary conditions - Koprubasi, Turhan; Yokus, Nihal (Informa UK Limited, 2017)
In this paper, we study the principal functions corresponding to the eigenvalues and the spectral singularities of the boundary value problem (BVP) where and are complex sequences, , and is a eigenparameter.
Keywords: Discrete equations; eigenparameter; eigenvalues; principal functions; spectral analysis; 16. Peace & justice